1981
DOI: 10.2307/1961369
|View full text |Cite
|
Sign up to set email alerts
|

The Election of Blacks to City Councils: Clarifying the Impact of Electoral Arrangements on the Seats/Population Relationship

Abstract: The notion that at-large elections for city council seats are discriminatory toward blacks has recently been attacked as empirically invalid. Recent studies have reached conflicting conclusions as to whether electoral arrangements or socioeconomic factors are the major influence on how proportionately blacks are represented. This article addresses this issue, using a regression-based analysis in which proportionality is treated as a relationship across cities with electoral structure as a specifying variable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(79 citation statements)
references
References 9 publications
2
77
0
Order By: Relevance
“…The vast majority of research attempting to answer this question has focused on the indirect effect of the VRA on black representation. In particular, building upon the large body of research demonstrating an association between single-member districts and minority representation (Bullock and MacManus 1993;Engstrom and McDonald 1981;Karnig and Welch 1982;Marschall, Ruhil and Shah 2010;Meier and England 1984;Trounstine and Valdini 2008), scholars have long hypothesized that electoral changes in covered jurisdictions would lead to increases in minority representation. Specifically, single-member districts (SMD) are argued to concentrate blacks into compact electoral districts, reducing their reliance upon other groups in the electorate and increasing their capacity to elect black candidates to legislative office.…”
Section: How? Explaining Black Gains In Council Representationmentioning
confidence: 99%
“…The vast majority of research attempting to answer this question has focused on the indirect effect of the VRA on black representation. In particular, building upon the large body of research demonstrating an association between single-member districts and minority representation (Bullock and MacManus 1993;Engstrom and McDonald 1981;Karnig and Welch 1982;Marschall, Ruhil and Shah 2010;Meier and England 1984;Trounstine and Valdini 2008), scholars have long hypothesized that electoral changes in covered jurisdictions would lead to increases in minority representation. Specifically, single-member districts (SMD) are argued to concentrate blacks into compact electoral districts, reducing their reliance upon other groups in the electorate and increasing their capacity to elect black candidates to legislative office.…”
Section: How? Explaining Black Gains In Council Representationmentioning
confidence: 99%
“…Several studies have identified the resources available to the black population as an important factor in helping minorities develop strategies to achieve their political goals (Engstrom and McDonald 1981), mobilize more minority voters (Browning, Marshall, and Tabb 1984), develop the leadership potential to sustain interest group activities (Giles and Evans 1985), and increase the supply of qualified minority candidates (Meier and Stewart 1991). At-large systems require black candidates to mobilize more voters across a larger geographic space, and given findings suggesting that AL systems impede the conversion of black resources to black school board seats (Robinson, England, and Meier 1985), we expect resources to be particularly salient in AL structures.…”
Section: Modeling Black Representationmentioning
confidence: 99%
“…Research posits that while black community resources are the most significant determinants of black political success (Bullock 1975;Kamig 1976Kamig , 1979Latimer 1979;Kamig and Welch 1980;Engstrom andMcDonald 1981, 1982;Bullock and MacManus 1987;Welch and Bledsoe 1988), a disproportionate amount of those resources are channeled toward the election of black men (Kamig andWelch 1980: 472;Sigelman and Sigelman 1982). Compounding lack of resources, voters may place a higher premium on district seats-given a choice between a man or a woman (Welch and Karnig 1979).…”
mentioning
confidence: 99%